Nutrient Cycling of Eucalyptus Plantation in Relation to Stand Age in Agroforestry System - Mohsin, Faiz; Singh, R. P.; Singh, K. (Indian Forester, 1996)
The annual litter production increased with increasing age of the Eucalyptus plantations both in the pure and intercropped stands with Mentha and Cymbopogon spp. An increase in litter production was recorded in all the intercropped in comparison to pure stands at all the ages. Higher concentration of N, P and K was observed in the litter of the intercropped stands which decreased with increasing ages of the stands. The total addition of nutrients through litterfall to the soil was higher in the intercropped than the pure stands. The N, P and K contents of the soil under the pure stands was higher than those of inter cropped stands. Maximum amount of N and K was found in the superficial layer of the soil which decreased with increasing depth. Most of the Phosphorus was accumulated in the soil at the depth of 15-30 cm in all the stands. The available N, P and K in the soil increased with increasing age of the stands.